2018
DOI: 10.21037/jtd.2018.06.104
|View full text |Cite
|
Sign up to set email alerts
|

Implications of obesity in cardiac surgery: pattern of referral, physiopathology, complications, prognosis

Abstract: A U-shaped relationship between body mass index (BMI) and outcomes emerged after cardiac surgery. This review analyses the physio pathologic basis of obesity related complications and evaluates prognostic implications. Both leaner and morbid obese should be considered pre-operatively rather than reactively and, when referred for elective surgery, should undergo a focused metabolic status management, and a thorough evaluation of health status. Adherence to sound surgical principles, and tailored patient blood m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 38 publications
1
28
1
11
Order By: Relevance
“…Obesity is also considered as an effective factor in the incidence of cardiovascular disease as well as pulmonary diseases. A review of various studies has shown that the incidence of PC following CABG surgery in obese patients is significantly higher than in other patients [28], but some studies have reported that the body mass index (BMI) of patients with and without PC was similar and the mean BMI in both groups was not statistically significant [26]. Diabetes mellitus (DM) as a prevalent underlying disease in different societies has always been a factor in the occurrence of varied morbidity and mortality.…”
Section: Preoperative Factorsmentioning
confidence: 99%
“…Obesity is also considered as an effective factor in the incidence of cardiovascular disease as well as pulmonary diseases. A review of various studies has shown that the incidence of PC following CABG surgery in obese patients is significantly higher than in other patients [28], but some studies have reported that the body mass index (BMI) of patients with and without PC was similar and the mean BMI in both groups was not statistically significant [26]. Diabetes mellitus (DM) as a prevalent underlying disease in different societies has always been a factor in the occurrence of varied morbidity and mortality.…”
Section: Preoperative Factorsmentioning
confidence: 99%
“…Kalp cerrahisi sonrası hasta sonuçlarını etkileyen önemli komplikasyonlardan biri de postoperatif böbrek yetmezliğidir ve literatürde sıklığının obezite ile arttığı, ancak diyaliz gereksiniminde anlamlı fark olmadığı gösterilmiştir [5,13,[15][16][17] . Mekanizması net olmasa da, değişen renin-anjiotensin-aldesteron sistemi, kronik inflamasyon, metabolik sendrom ve preoperatif HT/DM gibi komorbiditelerin varlığı suçlanmaktadır [5,16,17] . Sonuçlarımız da literatürle benzer şekilde postoperatif obez grupta renal yetmezlik insidansı yüksek, dializ gereksinimi benzer bulundu.…”
Section: Discussionunclassified
“…Yine iki farklı çalışmada da, obez olgularda kanama komplikasyonu ve buna bağlı re-operasyon oranlarının daha az olduğu gösterilmiştir [15,18] . Pek çok çalışmada obezitenin daha az kanamayla ilişkisi gösterilmiş ve bunun nedeni olarak, mediastende biriken büyük miktardaki yağ dokusu ve yüksek intraabdominal basıncın, intratorasik basıncı arttırarak kanama alanlarında kompresyon etkisi yaratması, açıklık kazanmasa da obeziteye bağlı hiperkoagülopatik durum ve daha az hemodilüsyon gereksinimi olarak bildirilmiştir [5,[13][14][15]17,18] . Bizim çalışmamızda da postoperatif drenaj miktarları benzer olsa da tamponad ve kanama sebepli cerrahi gereksinim obez grupta daha azdı.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Current estimates suggest that >35% of patients undergoing heart surgery are obese (body mass index (BMI) >30 kg/m 2 ) ( 1 ). Obesity is causally linked to the development of IR and T2DM which increases the risk for cardio metabolic disorders ( 2 4 ) as well as susceptibility of re-hospitalization ( 5 , 6 ). Predicting relapses of post-operative complications in obese patients who undergo cardiac surgery is significantly complicated by persistent metabolic maladaptation associated with obesity, such as increases in circulating lipids, glucose, adipocytokines (leptin, insulin, RBP4) and branch chain amino acids (BCAAs).…”
Section: Introductionmentioning
confidence: 99%